1994
DOI: 10.1136/bmj.309.6953.511
|View full text |Cite
|
Sign up to set email alerts
|

Water birth and infection in babies

Abstract: Outcome of gamete intrafallopian transfer in women of 40 and over according to whether the number of oocytes transferred was rstricted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 0 publications
1
22
2
6
Order By: Relevance
“…Contrary to expectations and contrary to the small amount of literature that exists on the subject [29,30], infections of the neonate after waterbirths were not more frequent than in other birth methods. A strong dilution of the micro-organism is obtained by the large quantity of water contained in our tubs (560 liters) and by continual water renewal.…”
Section: Watercontrasting
confidence: 42%
“…Contrary to expectations and contrary to the small amount of literature that exists on the subject [29,30], infections of the neonate after waterbirths were not more frequent than in other birth methods. A strong dilution of the micro-organism is obtained by the large quantity of water contained in our tubs (560 liters) and by continual water renewal.…”
Section: Watercontrasting
confidence: 42%
“…The advantages of immersion in water during labour and/or birth include reduced pain, increased functional diameter of the true pelvis, increased quality of contractions, increased release of endorphins, decreased need for opiates, increased movement for the mother as well as improved positioning in different stages of labour (6). There are also studies that have reported the disadvantages associated with water birth which include maternal and neonatal infections, as well as the possibility of respiratory problems for the newborn (7,8). Cluett and Burns in a review of 11 trials concluded that water immersion during the first stage of labour reduced the use of epidural/spinal analgesia, but there was limited data for other outcomes related to water use during the first and second stages of labour (9).…”
Section: Abstract öZetmentioning
confidence: 99%
“…Im mer wie der wird kri tisch auf eine er höh-te In fek ti ons ge fahr bei der Was ser ge burt v. a. für das Neu ge bo re ne hin ge wie sen [22,23]. Un strit tig und je dem Ge burts helfer aus ei ge ner An schau ung be kannt ist, dass vor al lem im Rah men der Press pe riode häu fig Stuhl von der Ent bin den den abge setzt wird, der in der Fol ge na tür lich das Was ser ver un rei nigt.…”
Section: In Fek Ti Ons Ge Fahrunclassified